2012
DOI: 10.1177/0149206312455245
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Limitations and Future Directions in Scholarly Reports

Abstract: The authors content analyzed self-reported limitations and directions for future research in 1,276 articles published between 1982 and 2007 in the Academy of Management Journal, Administrative Science Quarterly, the Journal of Applied Psychology, the Journal of Management, and the Strategic Management Journal. In order of frequency, the majority of self-reported limitations, as well as directions for future research, pertains to threats to internal, external, and construct validity issues, and there is a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(138 citation statements)
references
References 87 publications
8
122
0
Order By: Relevance
“…Our results have several implications for replication studies using qualitative research, as well as for authors and journal editors and reviewers in terms of how to enhance the transparency of qualitative research in the future. Also, improved replicability is likely to lead to improvements in quality because manuscripts that are more transparent allow for a more trustworthy assessment of a study's contributions for theory and practice (Brutus, Aguinis, & Wassmer, 2013). Specifically regarding managerial practices, increased transparency means that if organizations implement policies and actions closely based on detailed and open information available in published research, they are more likely to produce results consistent with those reported in the articles.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have several implications for replication studies using qualitative research, as well as for authors and journal editors and reviewers in terms of how to enhance the transparency of qualitative research in the future. Also, improved replicability is likely to lead to improvements in quality because manuscripts that are more transparent allow for a more trustworthy assessment of a study's contributions for theory and practice (Brutus, Aguinis, & Wassmer, 2013). Specifically regarding managerial practices, increased transparency means that if organizations implement policies and actions closely based on detailed and open information available in published research, they are more likely to produce results consistent with those reported in the articles.…”
Section: Discussionmentioning
confidence: 99%
“…We discuss the evidence and implications regarding our proposed DAM in employee turnover research and provide an agenda for the future study of turnover. Although some of these individual suggestions may sound like conventional wisdom, a recent review of limitations and future research directions in the discussion sections of 514 OB articles in five top management journals found that authors reported a mean of 1.63 limitations and 1.36 future research directions, with the majority focused on internal validity issues (Brutus et al, ). Our content analysis suggests that such minor mentions are having little impact on research practice.…”
Section: Discussionmentioning
confidence: 99%
“…Boundary conditions describe to what extent findings can be generalized to situations other than the one(s) studied. Limitations and boundary conditions should be reported in such a way that readers can understand the consequences of those limitations for the interpretation of results (Brutus, Aguinis, & Wassmer, ). Finally, the findings should be discussed in light of effect sizes found in earlier research (in a meta‐analytical sense).…”
Section: About the Rigor Of Future Psm Researchmentioning
confidence: 99%